Rome and Women’s Response to Crisis: from Early Christianity to the Present Day - Kinga Araya (Acta ad Archaeologiam et Artium Historiam Pertinentia, 2024)
This article presents a research project conducted by nine scholars that culminated in a publication. As Project Leader, I had the privilege of coordinating this interdisciplinary, bilingual, and inter-university group entitled Rome and Women’s Response to Crisis: from Early Christianity to the Present Day, which critically examines - from a spiritual, socio-political, and cultural perspective - the stories of heroic Roman women who bravely confronted the crises of their time, from the earliest days of Christianity to the present. In addition to exploring the historical, socio-political, cultural, and spiritual contexts in which these heroic female protagonists lived and worked, the authors of the essays also emphasise – in explicit or implicit ways - the critical role which the theological virtues of faith, hope, and charity played in their lives and cardinal virtues of fortitude, prudence, justice, and temperance. There is also a captivating reading on Saint Catherine of Siena’s virtue of patience. Nevertheless, it is not only through the lens of moral excellence that we learn about ordinary women living extraordinary lives as sisters, spouses, virgins, and mothers - both natural and spiritual. Towards the end of the article, there are passages drawn from Andrea Donati’s contribution about Vittoria Colonna, one of the early modern protagonists to whom the Symposium was dedicated.